Surface potential and roughness controlled cell adhesion and collagen formation in electrospun PCL fibers for bone regeneration - Sara Metwally; Sara Ferraris; Silvia Spriano; Zuzanna J. Krysiak; Łukasz Kaniuk; Mateusz M. Marzec; Sung Kyun Kim; Piotr K. Szewczyk; Adam Gruszczyński; Magdalena Wytrwal-Sarna; Joanna E. Karbowniczek; Andrzej Bernasik; et al. (Materials & Design, 2020)
Surface potential of biomaterials is a key factor regulating cell responses, driving their adhesion and signaling in tissue regeneration. In this study we compared the surface and zeta potential of smooth and porous electrospun polycaprolactone (PCL) fibers, as well as PCL films, to evaluate their significance in bone regeneration. The ’ surface potential of the fibers was controlled by applying positive and negative voltage polarities during the electrospinning. The surface properties of the different PCL fibers and films were measured using X-ray photoelectron spectroscopy (XPS) and Kelvin probe force microscopy (KPFM), and the zeta potential was measured using the electrokinetic technique. The effect of surface potential on the morphology of bone cells was examined using advanced microcopy, including 3D reconstruction based on a scanning electron microscope with a focused ion beam (FIB-SEM). Initial cell adhesion and collagen formation were studied using fluorescence microscopy and Sirius Red assay respectively, while calcium mineralization was confirmed with energy-dispersive x-ray (EDX) and Alzarin Red staining. These studies revealed that cell adhesion is driven by both the surface potential and morphology of PCL fibers. Furthermore, the ability to tune the surface potential of electrospun PCL scaffolds provides an essential electrostatic handle to enhance cell-material interaction and cellular activity, leading to controllable morphological changes.